Protecting the Herd: Why Pharmacists Matter in Mass Vaccination - Lois Lee; Gregory M. Peterson; Mark Naunton; Shane Jackson; Mary Bushell (Pharmacy, 2020)
Background: The COVID-19 pandemic is ongoing. The unprecedented challenges worldwide implore the urgent development of a safe and effective COVID-19 vaccine. Globally, pharmacists have been delivering important public health services as part of the COVID-19 response. It remains to be seen what role they will play once a vaccine is available. This review examines herd immunity and the potential role of the pharmacy profession in mass vaccination against COVID-19, particularly within the Australian context. Aim: A literature review was conducted to review the global development of COVID-19 vaccines, and the Australian healthcare workforce capability and existing policy for mass vaccination and the potential role of the pharmacist. Method: ScienceDirect, Scopus, The National Centre for Biotechnology Information (NCBI), Wiley Online Library, PubMed, and Google Scholar were used to search for relevant literature using keywords COVID-19, vaccines, immunisation, herd immunity, pandemic, pharmacist and Australian healthcare. Results: A large portion of the literature was journal articles, and information from governmental and international bodies such as the World Health Organisation were often referenced. Over 20 million Australians need to be immunised through vaccination or acquire immunity through natural infection for the country to achieve herd immunity for COVID-19. When examining state and territory pandemic plans, pharmacists are underutilised. Modifying legislation to allow pharmacists to administer approved COVID-19 vaccines will enable a trained and skilled workforce to be deployed to increase the rate of mass vaccination. Conclusion: In preparation for a successful COVID-19 vaccine, the Australian Government must consider various elements in their vaccination policy. This includes the estimated herd immunity threshold, methods of vaccine delivery, vaccine clinic locations, staffing arrangements and training, and strategies for vaccine prioritisation. Pharmacists can and should play a key role in the roll out of mass COVID-19 vaccination.